Analisis Kecemasan dan Kepercayaan Diri Pra-Pertandingan pada Atlet Futsal Putra - Ananda Michael Firdaus; Pudjiijuniarto Pudjiijuniarto; Andun Sudijandoko; Catur Supriyanto (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Research Objectives: Mental and psychological health are key assets for athletes to achieve success. One psychological aspect is self-confidence and anxiety prior to a match. Currently, these aspects significantly influence an athlete's ability to understand the game pattern. Therefore, knowledge regarding anxiety and self-confidence in athletes before a match begins is necessary. Purpose : This study aims to determine the levels of anxiety and self-confidence among male futsal athletes before a match. Methods: The methodology employed is quantitative descriptive, utilizing a questionnaire comprising 31 items administered to 12 male futsal athletes. Data were analyzed descriptively using percentages and categorized according to the categories corresponding to each score obtained. Results will be presented using tables and frequency diagrams. Results: The study found that 75% of athletes still had high anxiety levels and 75% had high self-confidence levels. The lowest anxiety score was 8.33%, and self-confidence scores were in the high and very high categories. Conclusion: It is recommended that athletes regularly engage in mental training to reduce anxiety levels and maintain and enhance self-confidence, thereby optimizing performance during matches. Additionally, further research is needed involving a larger and more diverse sample, including gender differences, to identify other influencing factors.